2020
DOI: 10.3390/molecules25061432
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features of Triethylammonium Acetate through Molecular Dynamics

Abstract: I have explored the structural features and the dynamics of triethylammonium acetate by means of semi-empirical (density functional tight binding, DFTB) molecular dynamics. I find that the results from the present simulations agree with recent experimental determinations with only few minor differences in the structural interpretation. A mixture of triethylamine and acetic acid does not form an ionic liquid, but gives rise to a very complex system where ionization is only a partial process affecting only few m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…This is because C 2 VIm + tend to be planar and the presence of P[C 2 VIm] + aggregation. The d p is assigned to the correlation distance of pedant group to pedant group (d p ) and can be calculated by the Bragg function d p = 2π/q p [ 19 ]. The order of the value of d p is d p P[DADMA][PF6] (0.472 nm) ≥ d p P[VBTMA][PF6] (0.470 nm) > d p P[C2VIm][PF6] (0.426 nm).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because C 2 VIm + tend to be planar and the presence of P[C 2 VIm] + aggregation. The d p is assigned to the correlation distance of pedant group to pedant group (d p ) and can be calculated by the Bragg function d p = 2π/q p [ 19 ]. The order of the value of d p is d p P[DADMA][PF6] (0.472 nm) ≥ d p P[VBTMA][PF6] (0.470 nm) > d p P[C2VIm][PF6] (0.426 nm).…”
Section: Resultsmentioning
confidence: 99%
“…This reveals that the real number of free PF 6 − contributing to conductivity is not in accordance with this because of different ion-pair complexation interaction energy ( E c ) [ 24 ]. The value of E c can be calculated by DFT with Gaussian program by considering the different electronegativity of atoms and charge distribution of anion and cation in the real PIL structure as shown in Figure 8 [ 19 , 32 ]. Restrained electrostatic potential (RESP) atomic charges are obtained with Multiwfn program [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large DpKa leads to highly ionized liquids, a small one leads to a partially neutral system with the possible occurrence of phase separation of the volatile neutral components. [114][115][116] In all intermediate cases, however, the metric based on pKa is not conclusive as one can realize by observing the different ionicity degrees obtained by mixing acetic acid and different amines with similar pKa. 117 Even in homologous series of PILs, ionicity (hence viscosities and conductivities which are strictly related to it) do not show a clear relation with pKa, 118 but rather with the ability of the ensuing fluid to (self-)solvate the ions, 119 with the proton affinities of the bases, 120 and with other thermodynamics factors such as the entropy change associated with reaction (1).…”
Section: The Problem Of Ionicitymentioning
confidence: 96%
“…In a recent work, backed up by experimental evidence, we have shown that this is not the case. 114,115 In its pure form, TEAAc is a liquid composed by roughly two thirds of neutral molecules which solvate the remaining third of the ions. A pictorial way to represent this situation is reported in Figure 5.…”
Section: The Problem Of Ionicitymentioning
confidence: 99%